Los puntos de encuentro familiar y el derecho de los menores a mantener una relación con sus progenitores - Blanco Carrasco, Marta (Cuadernos de Trabajo Social, 2008)
One of the recognised rights of minors, not only internationally, but also in Spain, is the right to maintain a relationship with their parents. The increase in legal separations and divorces and the conflict involved in these processes has shown that judicial response is not sufficient in some situations. Thus, certain resources, such as Family Meeting Points have arisen in order to facilitate the normalization of minors’ relationships with the other members of their families, through the intervention of professionals who are specially trained in these areas.
Keywords: Minors; Visiting rights; Mediation; Social resources